2007
DOI: 10.1111/j.1468-3148.2007.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Attribution Theory Applied to Helping Behaviour Towards People with Intellectual Disabilities Who Challenge

Abstract: Introduction Attribution theory posits that helping behaviour is determined in part by the potential helper's attributions and emotions regarding the behaviour that requires help. Specifically, helping is considered to be more likely if stability is perceived as low, generating optimism for change, and if controllability is perceived as low, engendering high levels of sympathy and low levels of anger. Method We conducted a systematic literature search to identify studies that have tested these predictions in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 43 publications
(137 reference statements)
1
55
1
Order By: Relevance
“…Although there was a highly significant difference in attributions of control when low levels of physical aggression were present, as opposed to absent, at higher frequencies this difference was not as marked. One possible explanation for this is that for high frequency behaviours attribution theory may not be applicable as staff can habituate to them (Willner & Smith 2008). It could be speculated that staff would therefore attribute such habitual behaviours as being less under individual control.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a highly significant difference in attributions of control when low levels of physical aggression were present, as opposed to absent, at higher frequencies this difference was not as marked. One possible explanation for this is that for high frequency behaviours attribution theory may not be applicable as staff can habituate to them (Willner & Smith 2008). It could be speculated that staff would therefore attribute such habitual behaviours as being less under individual control.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers (Lucas et al 2009;Willner and Smith 2008) have suggested that the discrepancy between theory and praxis found in their research might be because attribution theory has largely been grounded on vignette data rather than observations of real-life interactions. However, vignette methodology has been shown to be suited for investigating the cultural context in which mental disorders and other stigmatized conditions of being are experienced (Pescosolido et al 2008;Coleman et al 2009).…”
Section: Study Limitationsmentioning
confidence: 94%
“…Weiner (1986) proposed that helping behaviour was more likely to occur when the stability of the behaviour was deemed to be low, therefore increasing optimism for change and when controllability of the behaviour by the individual was also deemed to be low, resulting in higher levels of sympathy and low levels of anger. Weiner's model has been challenged methodologically and considered to be only of relevance to low-frequency behaviours (Willner and Smith, 2008). It therefore may not be the best model to apply in child and family social work settings given social workers' tendency to habituate to displays of violence due to its high frequency (Virkki, 2008).…”
Section: Introductionmentioning
confidence: 99%